CT colonography in detection of colorectal carcinoma - Sofić, Amela (Radiology and oncology (Ljubljana), 2010)
Background. Diagnostic methods used in screening and detectingand 2 lipomas,and 2 lipomas, among tumours there were 55 adenocarcinomas and 1 lymphoma. Results showed CT colonography among tumours there were 55 adenocarcinomas and 1 lymphoma. Results showed CTsensitivity to polyps to be 89.7%, barium enema 48.7%, and colonoscopy 94.9%. Sensitivity to tumours of CT colonography colonography colorectal CT barium enema followed by colonoscopy wereand colonoscopy was 100% and of barium enema 94.6%. Specificities and PPV were 100% in all procedures. The performed. After thesensitivity to polyps to be 89.7%, barium enema 48.7%, andcomfort assessment showed CT colonography as the far most comfortable out of three procedures. colonoscopy 94.9%. Sensitivity to tumours of CT colonography procedures a comfort assessment was done in all colonography. The aim of thisand colonoscopy was 100% and of barium enema 94.6%. Specificities and PPV were 100% in all procedures. The study was to establish diagnostic accuracy andpatients. Diagnostic positive comfort assessment showed CT colonography as the far most comfortable out of three procedures. results were verified by the pato-histological examination. Sensitivity, specificity, positive comfort of CT colonography compared carcinoma are digitorectal examination,topredicative value (PPV) and negative predicative value (NPV) were calculated for each procedure.
Keywords: danka; debelo črevo; diagnostika; kolonoskopija; kolorektalne novotvorbe; računalniška tomografija; rak (medicina)